1999
DOI: 10.1016/s0002-9440(10)65266-2
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Mediates Orthopedic Implant Osteolysis

Abstract: Osteolysis complicating arthroplasty reflects progressive generation of implant-derived wear particles, which prompt an inflammatory reaction attended by recruitment of osteoclasts to the prosthesis-bone interface. To identify a soluble mediator of periprosthetic osteolysis we first showed that implant particles induce c-src in murine bone marrow macrophages (BMMs), a protein specifically expressed when these cells commit to the osteoclast phenotype. The fact that tumor necrosis factor-alpha (TNF) is a potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
283
1
8

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 369 publications
(305 citation statements)
references
References 25 publications
13
283
1
8
Order By: Relevance
“…Thus, there is evidence that LPS is a much stronger stimulator for activation of TNFa and NF-KB in macrophages in comparison to wear particles. The time courses of transactivation of TNFa promoter and secreted TNFa in this study are consistent to findings by Merkel et al [35]. They revealed that TNFa mRNA substantially escalates within 3 h of particle exposure after which it progressively declines.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, there is evidence that LPS is a much stronger stimulator for activation of TNFa and NF-KB in macrophages in comparison to wear particles. The time courses of transactivation of TNFa promoter and secreted TNFa in this study are consistent to findings by Merkel et al [35]. They revealed that TNFa mRNA substantially escalates within 3 h of particle exposure after which it progressively declines.…”
Section: Discussionsupporting
confidence: 92%
“…Our data support recent findings that the NF-KB signalling pathway may be involved in wear particleinduced periprosthetic osteolysis [16,18,35,41,45]. Our study extends these results and shows for the first time that not only TiAlV-, mixed-, or PMMA-particles [35,40], but also polyethylene-particles induce an activation of NF-KB signalling and the TNFa-promoter.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, osteolysis is correlated with higher wear rates, 4,5 abundant wear particles are associated with periprosthetic tissues recovered during revision surgery, [6][7][8] and implantation of wear debris can trigger osteolysis in animal models. [9][10][11][12][13][14] A common theme which has emerged is that a critical initiating event in wear debris action is activation of pro-inflammatory cytokine signaling within periprosthetic macrophages, which in turn leads to an imbalance in the levels of the key osteoclastogenesis regulators RANKL and OPG. [15][16][17][18] However, the precise molecular and cellular pathogenesis whereby prosthetic wear debris leads to osteolytic bone loss remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…lysis [11,12,15,27,30,35]. The osteoclastogenic action of these cytokines is thought to be primarily mediated through induction of the nuclear transcription factor NF-kB which is known to be essential for osteoclastogenesis [20].…”
mentioning
confidence: 99%